Internet addiction : a handbook and guide to evaluation and treatment - Young, Kimberly S.; Abreu, Cristiano Nabuco de (Hoboken, N.J. : John Wiley & Sons, 2010)
'Internet addiction is an emergent disorder in the psychiatric and psychological fields. This book provides a theoretical framework to understand how to define and conceptualize compulsive use of the Internet from a clinical perspective. With various theoretical models from the psychiatric, psychological, communication, and sociological fields, it explores the prevalence of the disorder and the most addictive or problematic online applications, such as online pornography, Internet gambling, and online games. Evidenced-based treatment approaches are provided as well. A must-have for every clinician'--Provided by publisher
Part II: Assessment and Treatment Methods. -- Chapter 8: What Makes Internet Use Addictive (Dr. David Greenfield (open topic...psycho-social-biological and cultural assessment) Licensed Psychologist and Director The Center for Internet and Technology Addiction Adjunct Faculty, University of Connecticut). -- Chapter 9: Psychotherapies in Treatment (Dr. Cristiano Nabuco de Abreu Professor of Psychology University of Sao Paulo, Brazil). -- Chapter 10: Working with Adolescents (Dr. Keith Beard Associate Professor of Psychology Marshall University). -- Chapter 11: Coping with Internet Infidelity (Dr. Monica Whitty School of Psychology Queen's University Belfast, Northern Ireland School of Applied Social and Human Sciences University of Western Sydney, Parramatta Campus, Australia). -- Chapter 12: Telematics and Virtual Therapy for Internet Addiction (Teuvo Peltoniemi, Communication Director Information Department of Finland Editor-in-Chief, AddictionLink and Intiimi Web Publication at the A-Clinic Foundation Helsinki Finland). -- Chapter 13: Inpatient Treatment and Rehabilitation( Dr. Randee McGraw/Shannon Chrismore Clinical Director Illinois Institute of Recovery Proctor Hospital, Peoria, Illinois). -- Chapter 14: Prevention and Education for Adolescents (Dr. Jung-Hye Kwon,Ph.D. Professor of Psychology Korea University). -- Chapter 15: Online Addiction: Psychotherapy and Systemic Dynamics with Adolescence Licensed Psychologist (Switzerland). -- Chapter 16: Conclusions (Drs. Cristiano Nabuco de Abreu and Kimberly Young)
Keywords: Behavior, Addictive -- diagnosis; Behavior, Addictive -- therapy; Internet additction- treatmenr